A comparative study on classification models for stock rating prediction - Yap, Justin; Wiradinata, Trianggoro (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2024)
The digital transformation in the stockbroker industry has led to a significant increase in retail investors, who often lack the expertise to analyse stocks thoroughly. This research addresses the challenge by proposing a classification model to predict stock ratings such as